THE EFFECT OF LEMONGRASS EXTRACT (Cymbopogon citratus L.) ON PEST MORTALITY OF Plutella xylostella L. IN MUSTARD PLANTS (Brassica juncea L.) - Moniharapon, Debby; Nindatu, Maria; Bastian, Alien (RUMPHIUS, 2021)
Cabbage leaf caterpillars (Plutella xylostella L., Lepidoptera: Plutellidae) are the main pests that are very damaging to Brassicaceae plants, especially cabbage, mustard greens, and caisin in Indonesia. The chemical content of lemongrass is citral, citronella, geraniol, mirsene, nerol, farnesol methil heptenol and dipentene. The purpose of this study was to determine the effective concentration of Plutella xylostella pest mortality and the right LC50 value of Plutella xylostella pest mortality. This research is experimental using a completely randomized design. The subjects were 50 plutella xylostella L. Instar III pests. The concentrations used were 10 g, 20 g, 30 g, 40 g with negative control 0 g (aquades) with 5 repetitions for each treatment group. Observations were made 24 hours after spraying and the results obtained were an increase in pest death with increasing concentration. Based on the results of analysis of variance seen in the calculated F value (41,962)> F table (2,866). This proves that the administration of lemongrass stem extract significantly influences the mortality of Plutella xylostella in mustard plants (Brassisca juncea). The results of LC50 probit analysis were obtained at the concentration of lemongrass extract at 21,277% with a lower limit of 17,782 and an upper limit of 24,824, meaning that at a concentration of 21,277% lemongrass extract was able to kill 50% of the Plutella xylostella pest used after 24 hours of administration at a 95% confidence level.